Fluorine-free synthesis of reduced graphene oxide modified anatase TiO2 nanoflowers photoanode with highly exposed 0 0 1 facets for high performance dye-sensitized solar cell. (15th November 2020) - Pugazhenthiran, N.; Mangalaraja, R.V.; Vijaya, S.; Suresh, S.; Kandasamy, M.; Sathishkumar, P.; Valdés, H.; Gracia-Pinilla, M.A.; Murugesan, S.; Anandan, S.
Graphical abstract: Highlights: Anatase TiO2 0 0 1 NFs were prepared by fluorine-free solvothermal method. TiO2 0 0 1 NFs were wrapped by reduced graphene oxide (RGO) charge transporter. RGO-TiO2 0 0 1 NFs were characterized by XRD, Raman, XPS, SEM and TEM. RGO-TiO2 0 0 1 NFs photoanode in DSSC exhibited improved efficiency of 6.78%. RGO-TiO2 0 0 1 NFs offered enhanced electron transport and reduced recombination. Abstract: A facile, fluorine-free and non-toxic one-pot solvothermal technique was adopted to synthesis TiO2 nanoflowers with anatase phase having 98% highly exposed 0 0 1 facets (TiO2 0 0 1 NFs). The morphology, grain size and crystallinity of pure TiO2 0 0 1 NFs and reduced graphene oxide (RGO) sheets modified TiO2 0 0 1 NFs (RGO-TiO2 0 0 1 NFs) were inspected by diffuse reflectance spectroscopy (DRS), X-ray diffractometry (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). TEM images showed the development of anatase TiO2 0 0 1 NFs with high crystallinity and uniform shape. The influence of RGO on the performance of the TiO2 0 0 1 NFs as a photoanode material in dye-sensitized solar cell (DSSC) was examined. High energy conversion efficiency (ɳ) was observed for the DSSC based on a photoanode made of RGO-TiO2 0 0 1 NFs when compared to DSSCs based on photoanodes fabricated using pure TiO2 0 0 1 NFs and commercial Degussa P25 TiO2, which exhibited η of 6.78, 4.59 and 2.71%, respectively. The improved performance of the DSSC based on a photoanode composed of RGO-TiO2 0 0 1 NFs was due to its good crystallinity, high dye intake and enhanced light-harvesting properties. Moreover, the presence of RGO greatly hindered the recombination of photogenerated electrons and increased their lifespan. This work discloses a novel efficient photoanode design for improving performance of the DSSCs.